Upaya Meningkatkan Kinerja Karyawan Melalui Desain Pekerjaan dan Lingkungan Kerja dengan Kepuasan Kerja Sebagai Variabel Intervening - Irmawati, Irmawati (Journal of Economics and Business UBS, 2024)
This study aims to investigate the relationship between job design, work environment, job satisfaction, and employee performance in an organization. These factors are considered to have an important role in creating optimal working conditions and encouraging employees to achieve high performance. The research method used is a survey with a quantitative approach. The respondents of this study were employees from several organizations in various industrial sectors. Data were collected through questionnaires adapted from instruments that have been tested for reliability. The results of data analysis showed a positive relationship between good job design and employee performance. This suggests that when job duties and responsibilities are clearly organized, employees have a better chance of achieving set performance goals. In addition, the results also show that a good work environment contributes positively to employee performance. Factors such as social support, adequate physical facilities, and a positive organizational culture can increase employee motivation and engagement, which in turn improves their performance. In conclusion, this study provides a more in-depth understanding of the relationship between job design, work environment, job satisfaction, and employee performance. This research is expected to provide guidance and recommendations for management practitioners to implement effective strategies to improve employee performance in their work environment.